Comparative evaluation of root canal obturation techniques and sealers in Diabetic Dentin: An in-vitro push-out bond strength test - Mevlüt Sinan Ocak; Mehmet Eskibağlar; Mustafa Gündoğar (PLoS ONE, 2026)
This study evaluated the comparative performance of different root canal obturation approaches using different sealing materials on the push-out bond strength of dentin samples obtained from patients with diabetes mellitus (DM). Forty single-rooted mandibular premolars were instrumented using the Reciproc R40 system and randomly assigned to four groups (n = 10 teeth each): (1) cold lateral compaction with AH Plus, (2) warm vertical compaction with AH Plus, (3) hydraulic single-cone obturation with gutta-percha and Bioserra sealer, and (4) sealer-only technique using the Bioserra bioceramic sealer. After storage at 37°C and 100% humidity for one week, 1-mm slices were prepared from the coronal, middle, and apical thirds and subjected to push-out testing. Data were analyzed using ANOVA and Tukey’s test (p < 0.05). Significant differences in push-out bond strength were observed among the obturation approaches using different sealer materials (p < 0.05). Bioceramic sealers exhibited higher bond strengths than epoxy resin–based sealers, particularly in the middle and apical thirds. Hydraulic single-cone and bioceramic sealer-only approaches outperformed conventional techniques (p < 0.001), whereas no significant difference was observed between cold lateral and warm vertical compaction techniques. Obturation approaches employing bioceramic sealers demonstrated superior bonding in diabetic dentin, suggesting potential advantages over conventional methods in the context of diabetic dentin.